(untitled) (Research, Society and Development, 2023)
This article presents a brief behavioral-analytic perspective on anxious behavior, through the film: Puss in Boots: The Last Order (2022). The objective of this article was to carry out an analysis of the film based on excerpts focusing on three main themes of analysis: Behavioral avoidance, Conditioned suppression and Coping repertoire deficits and how such elements relate to this class of response, in addition, they will be presented possible interventions that can be planned during therapy, with the child and/or their family members, aiming at a more comprehensive understanding of anxiety and its implications, as well as expanding coping repertoires. The methodology used was film content analysis with descriptive objectives. The excerpts were analyzed through a behavioral analytical perspective and organized into triple contingencies and correlated with the literature that discusses the topic, in addition to presenting possible clinical intervention strategies based on the film. The results highlighted a series of contingencies that establish relationships between anxious behavior and the thematic focuses of analysis in this article. It was concluded through the analyzes that the main character presented a series of avoidance behaviors after a certain aversive event, culminating in a considerable increase in the avoidant repertoire and concomitant suppression of operant behaviors. Furthermore, it was evidenced that the expansion of the repertoire of social skills was fundamental in tackling the problem presented.